Conversion from manual to automated cataloging system in selected academic and special libraries in Metro Manila a case study - Bondoc, Myrna S. (1998)
The purpose of this study was to document the various experiences of selected academic and special libraries in Metro Manila in converting from a manual to an automated system of cataloging and to prepare case studies for three of the libraries in the survey. The descriptive survey method was used with the questionnaire as a data-gathering tool for the survey while interview and observation were used for the case study.